PENGARUH MODEL SCRAMBLE BERBANTUAN WORDWALL TERHADAP KEMAMPUAN MEMBACA PERMULAAN SISWA KELAS 1 SD NEGERI 1 PAGAR AIR ACEH BESAR - Siti Hairani Siregar; Aida Fitri; Suci Fitriani (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Beginning reading ability is an essential foundation for elementary school students, particularly those in lower grades, in supporting their future learning success. However, there are still students who experience difficulties in recognizing letters and reading syllables, words, and simple sentences. These problems are influenced by the use of less varied learning models and the limited utilization of interactive learning media. Therefore, an innovative learning approach is needed to enhance students’ engagement and learning motivation, one of which is the implementation of the Scramble learning model assisted by Wordwall.This study aims to determine the effect of the Scramble learning model assisted by Wordwall on the beginning reading ability of first-grade students at SD Negeri 1 Pagar Air Aceh Besar. This research employed a quantitative approach using a Pre-Experimental Design in the form of a One Group Pretest-Posttest Design. The sample consisted of 25 students selected through total sampling technique. Data were collected using performance tests in the form of pretest and posttest. Data analysis was conducted through normality testing and Paired Samples t-test using SPSS version 26.The results showed that the mean pretest score was 49.40 and increased to 79.60 in the posttest. The significance value of 0.000 < 0.05 indicated that H₀ was rejected and Hₐ was accepted. Thus, the Scramble learning model assisted by Wordwall has a significant effect on students’ beginning reading ability.